The Influence of Digital Marketing on Training Selection Decisions and Productivity at The Bandung Vocational Training and Productivity Center - Marsilyn Pareda Tondonaung; Prihartono Aksan Halim (Greenation International Journal of Economics and Accounting, 2025)
Advancements in information technology in the digital era have encouraged vocational training institutions to implement digital-based marketing strategies to enhance promotional effectiveness and reach potential participants more broadly. This study aims to analyze the influence of digital marketing on training selection decisions and participant productivity at the Balai Besar Pelatihan Vokasi dan Produktivitas (BBPVP) Bandung. The research employed a quantitative approach with a cross-sectional survey design and involved a sample of 67 respondents selected using purposive sampling techniques. Data were collected through a Likert-scale questionnaire (1–5) and processed using SPSS version 25 through validity, reliability, normality tests, and Spearman correlation analysis. The results indicate that the implementation of digital marketing has a positive and significant effect on training selection decisions (r = 0.621; p = 0.000) and also significantly influences participant productivity (r = 0.635; p = 0.000). Furthermore, training selection decisions have a very strong relationship with increased participant productivity (r = 0.989; p = 0.000). The mean scores of all variables fall into the high category, indicating that digital marketing is considered effective in attracting public interest and improving training outcomes. Thus, digital marketing strategies play an essential role in increasing participation and competence among training participants at BBPVP Bandung. This study recommends optimizing the use of digital media as an effort to enhance the attractiveness and effectiveness of vocational training implementation.